Modeling Earth Systems and Environment - Modeling Earth Systems and Environment (Springer Nature, 2026)
The peer-reviewed journal Modeling Earth Systems and Environment (MESE) provides a unique publication platform by discussing interdisciplinary problems and approaches through modeling. The focus of MESE is on modeling in earth and environment related fields, such as: earth and environmental engineering; climate change; hydrogeology; aquatic systems and functions; atmospheric research and water; land use and vegetation change; modeling of forest and agricultural dynamics; and economic and energy systems. Furthermore, the journal combines these topics with modeling of anthropogenic or social phenomena and projections to be used by decision makers.
FI 0.51
Q3
Keywords: Earth; Space & Environmental Sciences; Earth Sciences; Ciencias de la Tierra; Acuerdos transformativos; Transformative agreements; Ingeniería de la Tierra; Cambio climático; Hidrogeología; Sistemas y funciones acuáticas